Renal cystic disease proteins play critical roles in the organization of the olfactory epithelium. - Jennifer L Pluznick; Diego J Rodriguez-Gil; Michael Hull; Kavita Mistry; Vincent Gattone; Colin A Johnson; Scott Weatherbee; Charles A Greer; Michael J Caplan (PLoS ONE)
It was reported that some proteins known to cause renal cystic disease (NPHP6; BBS1, and BBS4) also localize to the olfactory epithelium (OE), and that mutations in these proteins can cause anosmia in addition to renal cystic disease. We demonstrate here that a number of other proteins associated with renal cystic diseases - polycystin 1 and 2 (PC1, PC2), and Meckel-Gruber syndrome 1 and 3 (MKS1, MKS3) - localize to the murine OE. PC1, PC2, MKS1 and MKS3 are all detected in the OE by RT-PCR. We find that MKS3 localizes specifically to dendritic knobs of olfactory sensory neurons (OSNs), while PC1 localizes to both dendritic knobs and cilia of mature OSNs. In mice carrying mutations in MKS1, the expression of the olfactory adenylate cyclase (AC3) is substantially reduced. Moreover, in rats with renal cystic disease caused by a mutation in MKS3, the laminar organization of the OE is perturbed and there is a reduced expression of components of the odor transduction cascade (G(olf), AC3) and α-acetylated tubulin. Furthermore, we show with electron microscopy that cilia in MKS3 mutant animals do not manifest the proper microtubule architecture. Both MKS1 and MKS3 mutant animals show no obvious alterations in odor receptor expression. These data show that multiple renal cystic proteins localize to the OE, where we speculate that they work together to regulate aspects of the development, maintenance or physiological activities of cilia.